Thirteen ways of looking at a black man - Gates, Henry Louis Jr. 1950- (Random House, 1997)
As some remarkable men talk about their lives, many perspectives emerge. All these men came from modest circumstances and all achieved preeminence. They are people, Gates writes, "who have shaped the world as much as they were shaped by it, who gave as good as they got." Three are writers-- James Baldwin was once regarded as the intellectual spokesman for the black community; Anatole Broyard chose to hide his black heritage so as to be seen as a writer on his own terms; and Albert Murray rose to the pinnacle of literary criticism. General-turned-political-figure Colin Powell discusses his interactions with three presidents; entertainer Harry Belafonte's career has been distinct from his fervent activism; dancer and choreographer Bill T. Jones' fierce courage and creativity have continued in the shadow of AIDS; and religious leader Louis Farrakhan continues to attract controversy.--From publisher description.
Keywords: Mann; Mannen; Negers; Stereotyp; Schwarze; African American men; USA; Aufsatzsammlung; Biografie